IMPLEMENTASI FILM ANIMASI NUSSA DAN RARA UNTUK MENINGKATKAN BAHASA EKSPRESIF ANAK USIA DINI 5-6 TAHUN TK AISYIYAH 57 SURABAYA - Ardini, Savira Aulia Putri; Yunitasari, Anisa (MOTORIC, 2023)
In the age range from birth to six years of child development is so rapid, one aspect of development that early childhood has is language development. Language development is one of the important concerns in Early Childhood. This research was conducted with the aim of knowing the increase in expressive language skills of group B2 children at TK Aisyiyah 57 Surabaya after using the media of the animated films Nussa and Rara. This type of research is Classroom Action Research which consists of two cycles, each cycle being held in two meetings. The results of this study can be concluded that expressive children's language skills in group B2 TK Aisyiyah 57 Surabaya increased through the implementation of the Nussa and Rara animated films. The increase in expressive language skills can be seen from the average Pre-Action results of 37.86%, in the first cycle it increased by 63.71%, in the second cycle it reached 85.25% having achieved the very well developed (BSB) target criteria. So it can be concluded that there is an increase in the expressive language skills of group B2 children at TK Aisyiyah 57 Surabaya after using the implementation of the animated films Nussa and Rara. Keywords : Early Childhood, Expressive Language, Animated Film Media